Conflicted memory : military cultural interventions and the human rights era in Peru - Milton, Cynthia E. (Critical human rights., 2018)
What happens when concepts of "truth," "memory," and "human rights" are taken up and adapted by former perpetrators of violence? Peru has moved from the 1980s-90s conflict between its armed forces and Shining Path militants into an era of open democracy, transitional justice, and truth and reconciliation commissions. Cynthia Milton reveals how Peru's military has engaged in a tactical cultural campaign--via books, films, museums--to shift public opinion, debate, and memories about the nation's violent recent past and its part in it. Milton calls attention to fabrications of our post-truth era but goes further to deeply explore the ways members of the Peruvian military see their past, how they actively commemorate and curate it in the present, and why they do so. Her nuanced approach upends frameworks of memory studies that reduce military and ex-military to a predictable role of outright denial